Sun Safety Knowledge, Practices, and Attitudes in the West of Iranian Farmers in 2024: A Cross‐Sectional Study - Farzam Bidarpoor; Halimeh Farazandeh; Payman Ghaderi; Kamal Ebrahimi; Hassan Mahmoodi (Health Science Reports)
ABSTRACT Background and Aims Due to the high risk of skin cancer from sun exposure in farmers, understanding their awareness of preventive behaviors is critical. Therefore, this study aimed to determine awareness, attitudes, and practices regarding skin cancer prevention among Iranian farmers. Methods This cross‐sectional study was conducted using a valid questionnaire with 336 farmers randomly selected from villages in Kurdistan Province, Iran. To be eligible for the study, participants had to be 18 years of age or older and currently working on a farm in the study region. Results The mean age years of participants was 49.31 ± SD = 12.23. The mean ± SD of attitude and performance scores were 11.50 ± 3.78 (min = 2, max = 20) and 9.05 ± 2.48 (min = 0, max = 15), respectively. The findings indicate that while 90.2% of participants are aware of the risks of prolonged sun exposure, misconceptions remain. Only 46.4% recognize UV dangers on cloudy days, and 63.4% understand sunscreen use is needed beyond sunny conditions. Awareness of specific risks like skin cancer (42.6%) and sunburn (27.4%) is moderate, while knowledge of cataracts (6.8%) and premature skin aging (9.2%) is low. Barriers to sunscreen use persist, with only 22.3% deeming it important and 40.8% finding it convenient. The risk of developing skin cancer was underestimated in 131 (39.0%) participants. Conclusion Knowledge, attitudes, and practices regarding skin cancer prevention among farmers in Iran are low. There is a need for culturally appropriate educational messages and intervention programs to increase awareness, improve attitudes, and promote preventive behaviors among farmers.